Compras públicas centralizadas em situaç\~oes de emergência e calamidade pública - Eduardo P. S. Fiuza; Felippe Vilaça Loureiro Santos; Virginia Bracarense Lopes; Bernardo Abreu de Medeiros; Franklin Brasil Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The Covid-19 pandemic exposed the fragility of institutional supply arrangements to the world and sparked predatory competition among buyers. In this context, the rationalization of demand and use of medical inputs and the centralized management o these acquisitions are recommended strategies, and transposing them to the Brazilian scenario requires an appreciation of the challenges and opportunities available to public managers. Collaborative or joint purchases are one of the most effective instruments to reduce costs in healthcare systems, but neither cost reduction should be the sole objective, nor is the mere aggregation of purchases a necessary condition for such reduction. The state of public calamity instituted in February 2020 led to the rapid emergence of a provisional Law with a view to meeting more quickly and effectively the urgent needs for acquisitions and contracts, among which we highlight the provision for the use of bidding waivers in awarding frame contracts (Brazilian Price Registration System), the expansion of the use of the (more flexible) Differentiated Contracting Regime, introduction of advanced payments, and the temporary increase of the upper value threshold of the bidding waiver. However, progress may not be sufficient yet and it appears necessary to structure an innovative system for public procurement, such as the adoption of multi-supplier framework agreements. In this article, we outline three strategies to render them feasible, in addition to offering three operational deployment scenarios, according to the platform to be used (Siasg/Comprasnet or marketplace or both). The pandemic can be a great opportunity to accelerate convergence for these coordinated purchases
Keywords: H51; H57; K23; L65; L81; 330; public procurement; public tenders; Covid-19; pooled procurement; e-commerce; framework agreements; healthcare inputs; medical supplies